PROFIL KEHIDUPAN MASYARAKAT SUKU SAKAI DIDESA SEMUNAI KECAMATAN PINGGIR KABUPATEN BENGKALIS - Sellia, Ririn; Rianto, Slamet; Erita, Yeni (STKIP PGRI Sumbar, 2013)
This study aimed to obtain information, and describe profile data about the Community Life Sakai tribe in the village Semunai Uptown District Bengkalis seen from: (1) Education Sakai tribal society (2) The livelihoods of tribal communities Sakai (3) Revenue Society Sakai tribes (4) Peoples Habits Sakai tribe. This study is a qualitative study using interview techniques .To answer this problem used primary data and secondary data . Primary data was collected through observation, interviews, discussions with informants and photographs taken in the field, while the secondary data obtained from the relevant parties.The results showed: (1) The condition of public education in general Sakai tribe is not in school because first does not have a cost, but their kids have started school there, (2) The livelihoods of tribal communities Sakai is a fishing river, (3) income Sakai tribe at present uncertain , ranging from 25.000 - Rp 30,000 per day, (4) Habits Sakai tribal communities still exist such as food and the presence of potato manggalo show their customs such as curing a disease called berdikir.